Positioning in cyberspace: Evaluating bestselling authors' online communicated brand personalities using computer-aided content analysis - R. A. Opoku; L. F. Pitt; R. Abratt (South African Journal of Business Management, 2007)
This study employs a computer-aided text analysis technique to explore whether bestselling authors communicate Aaker's brand personality in the online environment. We argue that content analysis facilitated by a computer is relatively reliable and less tedious than that performed by human coders. We analyse the content of websites on the presumption that this reflects what the author wants to say about him/herself. The study offers a new technique for content analysts and marketing communicators to quantify various aspects of marketing communications and goes a little further towards the evaluation and mapping of websites using correspondence analysis.
Keywords: 650